Etika Advokasi Public Relations dalam Manajemen Krisis Reputasi - Indrayani, Heni (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2016)
AbstractIn handling the crisis company, Public Relations Proffesionals is required to balance the interests of companies and term of public interests. Public Relations Proffesionals often perform persuasion what course for sake of good company reputation. Here, ethics advocacy present into solutions dilematik between defending the interests of company and the public interests. In communicating to the public, Public Relations Proffesionals rests on a truth value, honesty, social responsibility, openness, loyalty, fair thinking, respect, integrity and communication frankly. The models of ethics in overcoming the crisis include Attorney Adversary Model, Two-way symmetrical model, Social Responsibility Model, Partisan versus Mutual Values Model, and Professional Responsibility Model. While ethical action Professional Public Relations in crisis management adhering to the code of professional conduct and codes of conduct to be able to behave or act as professionals in decision-making, and what procedures are done objectively, and be accountable.Â Keywords : Professional Public Relations, Advocacy ethics, Crisis Management